A curious case of chest wall lump turning out to be isolated primary cutaneous aspergillosis in an immunocompetent female: a case report - Kamat, Manmohan Madhukar; Singh, Neeraj Pratap; Nattey, Kartik; Shetye, Shravani; Barman, Seema (International Surgery Journal, 2019)
Aspergillosis is a fungal infection caused by certain types of mold. Although they are found commonly throughout nature, these molds normally don’t cause problems. Aspergillosis is an uncommon fungal infection in which primary cutaneous sites are very rare. Most cases occur in immunodepressed patients and are disseminated in the blood. We report a 32 year old female with primary cutaneous aspergillosis in an otherwise immunocompetent female with no other systemic manifestation. 32 year old female presenting with left lower chest lump fixated to chest wall. It was thought of as neoplasm clinically and radiologically mostly soft tissue neoplasm and was planned for wide excision of lump with segmental excision of involved rib segment. On histopathological examination of the specimen, it showed aspergillus organisms. It is a case of primary cutaneous manifestation of aspergillosis as fixed chest wall lump with otherwise no Broncho-pulmonary or systemic involvement in an immunocompetent patient. Primary cutaneous aspergillosis presenting as isolated chest wall lump without any Broncho pulmonary or systemic involvement in an otherwise immunocompetent individual is an extremely rare manifestation.